The Influence of The Marketing Mix on Educational Decision-Making is a Fascinating Area of Study - Sitorus, Budianto; Realize, Realize (Jurnal Ilmiah Manajemen dan Bisnis, 2024)
AbstractThis research employs a quantitative approach, utilizing a survey method as its chosen research design to investigate factors influencing students' decisions in choosing private junior high schools in Sekupang Subdistrict, Batam. Through the distribution of questionnaires to 159 students in the specified area, data is collected on various marketing mix components and their correlation with school choice decisions. The collected data undergoes rigorous multilinear regression analysis using the SPSS tool, employing statistical methods to test formulated research hypotheses and establish relationships between marketing mix variables and school choice decisions. The interpretation of results is presented, drawing meaningful conclusions and offering implications and recommendations for further development in the context of private junior high school selection. The final stage encompasses the meticulous creation of a research report adhering to scientific standards, comprehensively detailing the research stages, findings, data analysis, conclusions, and recommendations. This study contributes to a quantitative understanding of the multifaceted factors influencing students' decisions in the specified educational context.